2016
DOI: 10.4070/kcj.2016.46.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aortic Elasticity in Patients with Celiac Disease

Abstract: Background and ObjectivesCeliac disease (CD) is a chronic autoimmune disorder induced by dietary gluten intake by individuals who are genetically sensitive. Many studies report an increased risk of cardiovascular diseases in such patients. The aim of this study is to assess aortic elasticity properties in patients with CD that may be associated with an increased risk of cardiovascular disease.Subjects and MethodsEighty-one patients diagnosed with CD by antibody test and biopsy and 63 healthy volunteers were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…In untreated CD, aortic function can deteriorate, and this deterioration is predictive of subclinical atherosclerosis and future cardiovascular events[ 8 ]. Aortic strain and distensibility tend to be significantly lower, and the aortic stiffness index significantly higher, in untreated CD patients vs controls[ 8 , 10 ]. CD patients are at increased risk for coronary artery disease[ 9 ], which may have a genetic association[ 11 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…In untreated CD, aortic function can deteriorate, and this deterioration is predictive of subclinical atherosclerosis and future cardiovascular events[ 8 ]. Aortic strain and distensibility tend to be significantly lower, and the aortic stiffness index significantly higher, in untreated CD patients vs controls[ 8 , 10 ]. CD patients are at increased risk for coronary artery disease[ 9 ], which may have a genetic association[ 11 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
“…Correlation has been shown between restoration of the small intestinal villous atrophy and normalization of vascular parameters in gluten-abstinent CD patients[ 14 ]. Yet after onset of the GFD, the lack of a significant reduction in aortic elastic properties suggests that some risk of cardiovascular disease may persist[ 10 ]. Type 1 diabetic patients with early presence of micro- or macrovascular complications should always be screened for CD[ 15 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many organs or systems such as cardiac, neurological, bone, skin, liver, and endocrin may be involved in the course of CD (13)(14)(15)(16)(17)(18)(19). Although it is an intestinal autoimmune disease, as the diagnostic age of CD getting older, the disease presents itself with complaints that not directed to gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…2 Many studies have been conducted about the aortic elastic changes due to various diseases. [4][5][6][7][8][9][10][11] Bayar et al 4 found changes in arterial stiffness parameters in patients with celiac diseases compared with the healthy when Ülger et al 5 did not find any changes in asthma patients. In this regard, Bektaş et al 6 found a significant change in asthmatic patients compared with posttreatment asthmatic patients.…”
Section: Introductionmentioning
confidence: 97%